Study of Doppler velocities and their relationship with Magnetic field oscillations in the penumbra of Sunspots (2022)
Local oscillations of the Doppler Velocities in the penumbra of the sunspot AR12186 were studied. For thispurpose, the images were aligned using the Enhanced Correlation Coefficient (ECC), ECC+Rotation andthe method proposed by Griñón-Marín et al. (2020). The wavelet transform was used to extract the waveletpower. Analyzing the distribution of the oscillation periods of the wavelet powers locally and globally, nodominant period was identified in these powers. Also, an attenuation in the Doppler powers of 22,1% and41,6% was obtained with respect to the powers obtained through the ECC method obtained through theECC+Rotation method for the powers found using the the Griñón-Marín et al. (2020) method and ECCmethod. In addition, no clear correlation was found between the powers Doppler Velocities, and magneticfield strength at the line of sight for the three alignment methods.